Nanofiber membrane material for solid polymer electrolyte as well as preparation method and application of nanofiber membrane material

By introducing fluorine-containing segment polymers on electrospinned fiber membranes in situ polymerization to form nanofiber membrane materials, the problem of low conductivity of solid polymer electrolyte membranes at room temperature, narrow electrochemical windows, and poor mechanical properties at high temperatures is solved. , realizes high-performance solid-state lithium battery electrolyte material.

CN119518079APending Publication Date: 2025-02-25CHINA NAT PETROLEUM CORP

Patent Information

Application Number
CN202311079319.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing solid polymer electrolyte membranes have problems in the low room temperature ionic conductivity, narrow electrochemical windows, and poor high-temperature mechanical performance, which is difficult to meet the high-performance needs of lithium batteries.

Method used

The fluorine-containing segment polymer is introduced by in-situ polymerization on the base layer of the electrospinned fiber membrane to form a nanofiber membrane material, which improves its room temperature conductivity, electrochemical window and high temperature mechanical strength.

Benefits of technology

The high ionic conductivity of nanofiber membrane materials at room temperature, wide electrochemical windows and good mechanical properties at high temperatures are achieved, and it is easy to prepare and assemble into the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a nanofiber membrane material for a solid polymer electrolyte as well as a preparation method and application of the nanofiber membrane material. The nanofiber membrane material is prepared from the following raw materials: an electrostatic spinning fiber membrane and a polymer matrix, the polymer matrix comprises a polymeric monomer, a lithium salt and an initiator; the polymeric monomers comprise polyethylene glycol diacrylate and trifluoroethyl methacrylate. The room-temperature ionic conductivity, the electrochemical window and the high-temperature mechanical property of the nanofiber membrane material disclosed by the invention are all at relatively high levels in the field of solid polymer electrolyte, and the nanofiber membrane material is easy to prepare and assemble into a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and in particular relates to a nanofiber membrane material for solid polymer electrolytes, a preparation method and application thereof. Background Art

[0002] Lithium secondary batteries play an important role in energy storage in portable electronic devices, electric vehicles, and large-scale power grid energy storage. However, the organic electrolyte used in lithium-ion batteries is flammable and has the risk of leakage and combustion. Solid electrolytes have high thermal stability and no leakage risk, which greatly reduces the potential safety hazards of lithium batteries. Lithium batteries using solid electrolytes are also regarded as the next generation of energy storage batteries.

[0003] Solid electrolytes are divided into inorganic solid electrolytes and solid polymer electrolytes. Among them, the raw material and processing costs of solid polymer electrolyte membranes are lower, and they have the potential for large-scale production. However, the solid polymer electrolyte membranes based on PEO still have some problems, such as low room temperature ion conductivity; easy oxidation and decomposition under high voltage, narrow electrochemical window; easy softening of electrolyte membranes at high temperatures, reduced mechanical properties, etc. By using electrospinning to build a variety of polymers into nanofiber membranes and prepare solid electrolytes, a fast lithium ion transmission channel can be constructed, and the toughness and strength of membrane materials can be improved. CN111653821A composites polyimide electrospun fibers and modified siloxane polymers to obtain solid polymer electrolytes. The spinning process of polyimide fibers is relatively complicated, involving nitrogen purging, hot pressing, stage temperature rise control imidization and other steps, and cannot be formed in one step, which increases the difficulty of the process; at the same time, the final composite solid polymer electrolyte contains low molecular plasticizers, is not a fully solid electrolyte, and is less safe than a fully solid polymer electrolyte. CN114163589A uses a multi-nozzle electrostatic spinning method to prepare a solid polymer of a single ion conductor polymer and an ion conductive polymer containing inorganic particles, but the ion conductivity of the single ion conductor polymer is generally low and it is difficult to meet the requirements for room temperature use; the spinning process containing inorganic particles is often difficult to control and the process is difficult; at the same time, the single ion conductor polymer film is relatively brittle, which has a great impact on the film forming property of the electrolyte membrane and battery assembly. The existing solid polymer electrolyte related technologies have not been able to completely solve the problems of low room temperature conductivity, narrow electrochemical window, and poor high temperature mechanical properties of solid polymer electrolytes. Therefore, it is urgent to develop a solid polymer electrolyte nanofiber membrane material with excellent performance and easy preparation to solve the above problems. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a nanofiber membrane material for solid polymer electrolyte, a preparation method and application thereof. The nanofiber membrane material adopts an electrospun fiber membrane as a base layer, and introduces a fluorine-containing segment polymer on the base layer by in-situ polymerization, thereby effectively improving its performance in terms of room temperature conductivity, electrochemical window and high temperature mechanical strength, and is easy to prepare and assemble into a battery.

[0005] The first aspect of the present invention provides a nanofiber membrane material for solid polymer electrolyte, wherein the raw materials for preparing the nanofiber membrane include electrospun fiber membrane and polymer matrix; the polymer matrix includes polymerization monomer, lithium salt and initiator; the polymerization monomer includes polyethylene glycol diacrylate and trifluoroethyl methacrylate.

[0006] As a specific embodiment of the present invention, in the polymerized monomers, the mass ratio of polyethylene glycol diacrylate to trifluoroethyl methacrylate is 2 to 4:1, preferably 3:1.

[0007] As a specific embodiment of the present invention, the lithium salt includes any one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium hexafluorophosphate, and lithium perchlorate; preferably, the amount of the lithium salt is 20-35% based on the total weight of the polymerized monomer.

[0008] As a specific embodiment of the present invention, the material of the electrospun fiber membrane is selected from polyvinylidene fluoride and / or polyacrylonitrile; preferably, the preparation method of the electrospun fiber membrane comprises: electrospinning a solution of polyvinylidene fluoride and / or polyacrylonitrile, and then drying; preferably, the solvent of the solution is N,N-dimethylformamide and / or acetone; preferably, when the polymer is polyvinylidene fluoride, the solvent is a mixed solvent of N,N-dimethylformamide and acetone, and when the polymer is polyacrylonitrile, the solvent is N,N-dimethylformamide, or a mixed solvent of N,N-dimethylformamide and acetone; preferably, in the solution, the mass volume ratio of polyvinylidene fluoride and / or polyacrylonitrile to the solvent is 2g:10-15mL; preferably, the drying is drying at 50°C for more than 24h.

[0009] As a specific embodiment of the present invention, the initiator is any one of azobisisoheptanonitrile and azobisisobutyronitrile; preferably, the amount of the initiator is 1% based on the total weight of the polymerized monomers.

[0010] The second aspect of the present invention provides a method for preparing the aforementioned material, comprising: S11, stirring and mixing a polymer monomer, a lithium salt, an initiator and a solvent to obtain a precursor solution; S12, injecting the precursor solution into an electrospinning fiber membrane, reacting at a certain temperature for a certain time, and then drying; preferably, the reaction temperature is 60°C and the reaction time is 3h; preferably, the drying temperature is 50°C and the drying time is 24h.

[0011] A third aspect of the present invention provides a solid-state lithium battery comprising the aforementioned material.

[0012] The fourth aspect of the present invention provides a method for preparing the aforementioned solid-state lithium battery, comprising: S21, stirring and mixing a polymer monomer, a lithium salt, an initiator and a solvent to obtain a precursor solution; S22, injecting the precursor solution into an electrospinning fiber membrane, reacting it at a certain temperature for a certain time, and then drying it to obtain a nanofiber membrane material; S23, stacking and assembling the positive electrode sheet, the nanofiber membrane material and the negative electrode sheet in sequence; preferably, the reaction temperature is 60°C and the reaction time is 3h; preferably, the drying temperature is 50°C and the drying time is 24h.

[0013] A fifth aspect of the present invention provides a power device comprising the aforementioned solid-state lithium battery.

[0014] The sixth aspect of the present invention provides the use of the aforementioned material in the preparation of a solid-state lithium battery.

[0015] The beneficial effects of the present invention are:

[0016] The nanofiber membrane material provided by the present invention comprises raw materials for preparing an electrospun fiber membrane, polyethylene glycol diacrylate, trifluoroethyl methacrylate and lithium salt. Among them, the electrospun fiber membrane is used as a base layer to improve the mechanical strength of the nanofiber membrane material; polyethylene glycol diacrylate, trifluoroethyl methacrylate and lithium salt are used as polymer matrices. On the one hand, fluorine-containing segments can be introduced into the polymer, which decompose in the presence of trace water to form an anode passivation film rich in LiF at the electrode / electrolyte interface layer, which is beneficial to the chemical stability at the interface; on the other hand, a composite structure of a polyethylene glycol diacrylate-trifluoroethyl methacrylate cross-linked polymer containing lithium salt and an electrospun fiber membrane can be formed by a thermally induced double bond reaction. The reaction is simple and thorough, and very few impurities are introduced, which is beneficial to the cycle stability of the battery. The room temperature ionic conductivity, electrochemical window and high temperature mechanical properties of the nanofiber membrane material finally prepared by the present invention are at a relatively high level in the field of solid polymer electrolytes, and are easy to prepare and assemble into batteries. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Example 1

[0019] A nanofiber membrane material for solid polymer electrolyte, the preparation method comprising the following steps:

[0020] 1) Dissolve 2 g of PVDF in a mixed solvent of 5 mL of DMF and 5 mL of acetone at room temperature and stir for 6 h;

[0021] 2) electrospinning the PVDF solution, and peeling off the spinning membrane after 8 hours;

[0022] 3) Dry the spun membrane in a vacuum drying oven at 50°C for 24 hours;

[0023] 4) PEGDA1000, TFEMA, AVBN, and 30% lithium bis(trifluoromethanesulfonyl)imide are dissolved in tetrahydrofuran, the mass ratio of PEGDA1000 and TFEMA is 3:1, the mass fraction of lithium bis(trifluoromethanesulfonyl)imide is 20% of the total mass of PEGDA and TFEMA, and the mass fraction of AVBN is 1% of the total mass of PEGDA1000 and TFEMA. After stirring evenly, the mixture is injected into a dried spinning membrane to obtain a solid electrolyte precursor;

[0024] 5) heating the solid electrolyte precursor in a 60° C. forced air drying oven for 3 h to perform a polymerization reaction;

[0025] 6) The solid electrolyte nanofiber membrane after the polymerization is completely taken out, and is further dried in a vacuum drying oven at 50° C. for 24 h to obtain a solid polymer electrolyte nanofiber membrane material.

[0026] The obtained solid polymer electrolyte nanofiber membrane material for lithium batteries is a PEGDA-TFEMA cross-linked polymer containing lithium bis(trifluoromethanesulfonyl)imide and a PVDF nanofiber composite membrane, and the specific composition is LiTFSI-PEGDA-TFEMA-PVDF. The ionic conductivity of the obtained solid polymer electrolyte nanofiber membrane was tested, and the ionic conductivity was 1.69×10 -5 S cm -1The electrochemical window is 5.3 V at room temperature, and the tensile stress and elongation at break are 6.308 MPa and 3.2% respectively after standing at 60°C for 3 hours. It can be seen that the room temperature ionic conductivity, electrochemical window and high temperature mechanical properties of the solid polymer electrolyte nanofiber membrane material are at a relatively high level in the field of solid polymer electrolytes.

[0027] Example 2

[0028] A nanofiber membrane material for solid polymer electrolyte, the preparation method comprising the following steps:

[0029] 1) Dissolve 2 g of PAN in 10 mL of DMF at room temperature and stir for 6 h;

[0030] 2) electrospinning the PAN solution, and peeling off the spinning membrane after 8 hours;

[0031] 3) Dry the spun membrane in a vacuum drying oven at 50°C for 24 hours;

[0032] 4) PEGDA1000, TFEMA, AIBN, and 35% lithium bis(oxalatoborate) were dissolved in tetrahydrofuran, the mass ratio of PEGDA1000 to TFEMA was 3:1, the mass fraction of lithium bis(oxalatoborate) was 20% of the total mass of PEGDA and TFEMA, and the mass fraction of AIBN was 1% of the total mass of PEGDA1000 and TFEMA. After stirring evenly, the mixture was injected into a dried spinning membrane to obtain a solid electrolyte precursor;

[0033] 5) heating the solid electrolyte precursor in a 60° C. forced air drying oven for 3 h to perform a polymerization reaction;

[0034] 6) The solid electrolyte nanofiber membrane after the polymerization is completely taken out, and is further dried in a vacuum drying oven at 50° C. for 24 h to obtain a solid polymer electrolyte nanofiber membrane material.

[0035] The obtained cross-linked polymer membrane material for solid electrolyte of all-solid-state lithium battery is a PEGDA-TFEMA cross-linked polymer and PAN nanofiber composite membrane containing LiBOB, and the specific composition is LiBOB-PEGDA-TFEMA-PAN. The ionic conductivity of the obtained solid polymer electrolyte nanofiber membrane was tested, and the ionic conductivity was 1.35×10 -5 S cm -1 The electrochemical window is 4.9 V at room temperature, and the tensile stress and elongation at break are 6.015 MPa and 2.9% respectively after standing at 60°C for 3 hours. It can be seen that the room temperature ionic conductivity, electrochemical window and high temperature mechanical properties of the solid polymer electrolyte nanofiber membrane material are at a relatively high level in the field of solid polymer electrolytes.

[0036] Example 3

[0037] A nanofiber membrane material for solid polymer electrolyte, the preparation method comprising the following steps:

[0038] 1) Dissolve 2 g of PAN in a mixed solvent of 8 mL of DMF and 2 mL of acetone at room temperature and stir for 6 h;

[0039] 2) electrospinning the PAN solution, and peeling off the spinning membrane after 8 hours;

[0040] 3) Dry the spun membrane in a vacuum drying oven at 50°C for 24 hours;

[0041] 4) PEGDA1000, TFEMA, AIBN and 20% lithium perchlorate are dissolved in tetrahydrofuran, with the mass fraction of AIBN accounting for 1% of the mass of PEGDA1000 and TFEMA, and after being stirred evenly, the mixture is injected into the dried spinning membrane to obtain a solid electrolyte precursor;

[0042] 5) heating the solid electrolyte precursor in a 60° C. forced air drying oven for 3 h to perform a polymerization reaction;

[0043] 6) The solid electrolyte nanofiber membrane after the polymerization is completely taken out, and is further dried in a vacuum drying oven at 50° C. for 24 h to obtain a solid polymer electrolyte nanofiber membrane material.

[0044] The cross-linked polymer membrane material obtained for the solid electrolyte of all-solid-state lithium battery is LiClO 4 PEGDA-TFEMA cross-linked polymer and PAN nanofiber composite membrane, the specific composition is LiClO 4 -PEGDA-TFEMA-PAN, the ionic conductivity of the obtained solid polymer electrolyte nanofiber membrane was tested, and the ionic conductivity was 1.45×10 -5 S cm -1 The electrochemical window is 5.0 V at room temperature, and the tensile stress and elongation at break are 5.778 MPa and 2.8% respectively after standing at 60°C for 3 hours. It can be seen that the room temperature ionic conductivity, electrochemical window and high temperature mechanical properties of the solid polymer electrolyte nanofiber membrane material are at a relatively high level in the field of solid polymer electrolytes.

[0045] Comparative Example 1

[0046] In step 1), the solvent added was 20 mL of DMF, and the rest was the same as in Example 1.

[0047] The results showed that PVDF could not be spun into shape, and ultimately a solid polymer electrolyte nanofiber membrane could not be obtained.

[0048] Comparative Example 2

[0049] In step 4), PEGDA1000 and TFEMA were added in a mass ratio of 1:1, and the rest was the same as in Example 1.

[0050] The results showed that the final membrane material was very hard and brittle and could not be fully assembled into the battery.

[0051] Comparative Example 3

[0052] In step 4), PEGDA1000, TFEMA and AVBN are not added (equivalent to a solid electrolyte consisting of only PVDF fibers and lithium salt LiTFSI), and the rest is the same as in Example 1.

[0053] Finally, a solid polymer electrolyte nanofiber membrane was obtained. The ionic conductivity of the solid polymer electrolyte nanofiber membrane material was tested. Since the interface impedance between the PVDF fiber and the test electrode was too large, the effective conductivity could not be measured.

[0054] Comparative Example 4

[0055] Steps 1) to 3 are removed (equivalent to a solid electrolyte consisting of only lithium salt LiTFSI and polymer PEGDA-TFEMA cross-linked membrane), and the rest is the same as Example 1.

[0056] Finally, a solid polymer electrolyte nanofiber membrane was obtained. The ionic conductivity of the obtained solid polymer electrolyte nanofiber membrane material was tested, and its room temperature ionic conductivity was only 8.20×10 -6 S cm -1 .

[0057] Comparative Example 5

[0058] In step 1), PVDF was added but electrospinning was not performed, and the rest was the same as in Example 1.

[0059] Finally, a solid polymer electrolyte nanofiber membrane was obtained. The ionic conductivity of the obtained solid polymer electrolyte nanofiber membrane material was tested, and its room temperature ionic conductivity was only 3.56×10 -6 S cm -1 .

[0060] Comparative Example 6

[0061] In step 4), the mass fraction of lithium bis(trifluoromethanesulfonyl)imide added is 15% of the mass of PEGDA and TFEMA, and the rest is the same as in Example 1.

[0062] The results showed that the solid electrolyte precursor could not be polymerized, and ultimately a solid polymer electrolyte nanofiber membrane could not be obtained.

[0063] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A nanofiber membrane material for solid polymer electrolyte, characterized in that: The preparation raw materials include electrospun fiber membrane and polymer matrix; The polymer matrix includes a polymer monomer, a lithium salt and an initiator; The polymerizable monomers include polyethylene glycol diacrylate and trifluoroethyl methacrylate.

2. The material according to claim 1, characterized in that In the polymerizable monomers, the mass ratio of polyethylene glycol diacrylate to trifluoroethyl methacrylate is 2 to 4:1, preferably 3:

1.

3. The material according to claim 1, characterized in that The lithium salt includes any one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium hexafluorophosphate, and lithium perchlorate; Preferably, the amount of the lithium salt is 20-35% based on the total weight of the polymerized monomers.

4. The material according to claim 1, characterized in that The material of the electrospun fiber membrane is selected from polyvinylidene fluoride and / or polyacrylonitrile; Preferably, the preparation method of the electrospun fiber membrane comprises: electrospinning a solution of polyvinylidene fluoride and / or polyacrylonitrile, and then drying; Preferably, the solvent of the solution is N,N-dimethylformamide and / or acetone; Preferably, when the polymer is polyvinylidene fluoride, the solvent is a mixed solvent of N,N-dimethylformamide and acetone; when the polymer is polyacrylonitrile, the solvent is N,N-dimethylformamide, or a mixed solvent of N,N-dimethylformamide and acetone; Preferably, in the solution, the mass volume ratio of polyvinylidene fluoride and / or polyacrylonitrile to the solvent is 2 g:10-15 mL; Preferably, the drying is performed at 50° C. for more than 24 hours.

5. The material according to claim 1, characterized in that The initiator is any one of azobisisoheptanonitrile and azobisisobutyronitrile; Preferably, based on the total weight of the polymerized monomers, the amount of the initiator is 1%.

6. A method for preparing the material according to any one of claims 1 to 5, characterized in that: The preparation method comprises: S11, stirring and mixing the polymerization monomer, lithium salt, initiator and solvent to obtain a precursor solution; S12, injecting the precursor solution into the electrospinning fiber membrane, reacting at a certain temperature for a certain time, and then drying; Preferably, the reaction temperature is 60°C and the reaction time is 3h; Preferably, the drying temperature is 50° C. and the drying time is 24 hours.

7. A solid-state lithium battery, characterized in that: The solid-state lithium battery comprises the material according to any one of claims 1 to 5.

8. A method for preparing the solid-state lithium battery according to claim 7, characterized in that: The preparation method comprises: S21, stirring and mixing the polymerization monomer, lithium salt, initiator and solvent to obtain a precursor solution; S22, injecting the precursor solution into the electrospinning fiber membrane, reacting at a certain temperature for a certain time, and then drying to obtain a nanofiber membrane material; S23, stacking and assembling the positive electrode sheet, the nanofiber membrane material and the negative electrode sheet in sequence; Preferably, the reaction temperature is 60°C and the reaction time is 3h; Preferably, the drying temperature is 50° C. and the drying time is 24 hours.

9. A power device, characterized in that: It includes the solid-state lithium battery as described in claim 7.

10. Use of the material according to any one of claims 1 to 5 in the preparation of solid-state lithium batteries.

Citation Information

Patent Citations

  • Polyimide electrostatic spinning fiber modified siloxane composite solid polymer electrolyte and preparation and application thereof

    CN111653821A

  • Block polymer and preparation method thereof, block polymer electrolyte and preparation method thereof, and polymer lithium battery

    CN114163589A

Cited By

  • Single ion conduction solid polymer electrolyte membrane, preparation method thereof and lithium battery

    CN120637590A

  • Preparation method of high-ionic-conductivity polymer electrolyte based on beaded fiber structure

    CN122177922A